English adjective-noun compounds and related constructions - Bennett, Paul (Penerbit UKM, 2002)
The aim of this paper is to examine English constructions consisting of an adjective and a noun, with particular reference to whether this sequence can form a compound as well as a syntactic structure. Emphasis will particularly be placed on two kinds of examples: those where an adjective-noun structure modifies another noun, such as new-road enquiry; and those consisting of a relational adjective plus a noun, as in nervous disease. We shall touch on issues of productivity and lexicalization, as well as the relations and interactions between compounding and syntax.